Adoption level of improved wheat production technology in wheat-superzone, Kailali, Nepal - Udyan Devkota; Subodh Raj Pandey; Madav Prasad Neupane; Arun G.C. (Fundamental and Applied Agriculture, 2020)
The study was conducted to assess the impact of Prime Minister Agriculture Modernization Project (PM-AMP) on the level of adoption of improved wheat production practices among beneficiaries and non-beneficiaries of wheat superzone of Kailali district, Nepal in 2019. A total of 80 households, 50 beneficiaries of superzone and 30 non-beneficiaries were selected using simple random sampling technique and interviewed using a semi-structured interview schedule. Descriptive statistics, independent sample t-test, chi-square test and multiple linear regression model were used for data analysis using SPSS and MS-Excel. Pearson Chi-square test revealed the significant difference between beneficiaries and non-beneficiaries in access to extension agent and participation in training. Use of recommended variety and top-dressing of nitrogen fertilizer were found to be the most adopted practices while the use of recommended fertilizer dosage, irrigation practices and mechanization were found most ignored. The study showed a significant difference between beneficiaries and non-beneficiaries in the adoption of recommended variety, annual seed replacement, top-dressing of nitrogen fertilizer, recommended irrigation practice and weed management practices. The average adoption index was significantly higher for beneficiaries (0.4760) compared to non-beneficiaries (0.3367). The average wheat yield of the study area was 2.384 tons ha-1 and the average yield of beneficiaries (2.549 tons ha-1) was found to be higher than non-beneficiaries (2.109 tons ha-1). Multiple linear regression revealed that access to extension agent, disease control, adoption of treated seeds, mechanization, top-dressing of nitrogen fertilizer, amount of farmyard manure and urea were the major factors which determined the yield of wheat. Shortage of fertilizers was identified as the major problem. Among beneficiaries of superzone, 4% were reported to be highly satisfied, 54% were satisfied and 42% were dissatisfied with the activities of superzone. [Fundam Appl Agric 2020; 5(4.000): 500-512]